Risk Assessment on Convicted Child Sex Offenders in Iceland between 2001 – 2011. - Ingibjörg Johnson 1988- (2017)
Childhood sexual abuse (CSA) is a worldwide problem that cannot be condoned. Prevalance rates of CSA vacillate but strongly imply that the problem is exstensive. In Iceland, the situation is the same. In this study, 93 convicted male child sex offenders, who were convicted between 2001 and 2011, were subjected to a risk assessment using the Static-2002R scale. Their sentences were coded accordingly and a total score of risk of recidivism generated. Data from the Icelandic Prison and Probation Administration on the offender’s was obtained and examined in relation to their risk assessment score. Results demonstrated that the majority of convicted CSA offenders represent a low risk offender who offend outside of the family. The total number of victims that were victimized by the participants of this study was 139 and the majority of offenders had been prosecuted for offending against a single victim. The seriousness of victimization was coded and most victims had experienced an offence with seriousness level 2, which includes touching within clothing, oral sex and an attempted penetration. Recidivism rates were low, both when regarding general reoffending and child sexual offending. Recidivism rates were positively correlated to a total score of recidivism risk. Kynferðislegt ofbeldi gegn börnum er alþjóðlegt vandamál sem verður að uppræta. Tíðni þess er nokkuð á reiki en bendir til þess að vandinn sé víðtækur. Það sama virðist vera uppi á teningnum á Íslandi. Í þessari rannsókn voru 93 karlmenn, sem dæmdir hafa verið fyrir að brjóta kynferðislega gegn börnum, á árunum 2001-2011 metnir með áhættumatslistanum Static-2002R. Dómar þeirra voru kóðaðir samkvæmt listanum og heildarskor reiknað, sem gefur upp mat á áhættu þess að einstaklingur brjóti af sér aftur kynferðislega. Gögn voru fengin frá Fangelsismálastofnun ríkisins og borin saman við heildarskor þátttakenda á áhættumatslistanum. Niðurstöður sýndu að meirihluti dæmdra einstaklinga sem brjóta kynferðislega gegn börnum flokkast með lága áhættu og eru líklegri ...